Urbanization Impacts on Evapotranspiration Across Various Spatio‐Temporal Scales. Issue 8 (2nd August 2021) - Mazrooei, Amir; Reitz, Meredith; Wang, Dingbao; Sankarasubramanian, A.
Abstract: Urbanization has been shown to locally increase the nighttime temperatures creating urban heat islands, which partly arise due to evapotranspiration (ET) reduction. It is unclear how the direction and magnitude of the change in local ET due to urbanization varies globally across different climatic regimes. This knowledge gap is critical, both for the key role of ET in the energy and water balance accounting for the majority of local precipitation, and for reducing the urban heat island effect. We explore and assess the impacts of urbanization on monthly and mean annual ET across a range of landscapes from local to global spatial scales. Remotely sensed land cover and ET available at 1 km resolution are used to quantify the differences in ET between urban and surrounding non‐urban areas across the globe. The observed patterns show that the statistically significant difference between urban and non‐urban ET can be estimated to first order as a function of local hydroclimate, with arid regions seeing increased ET, and humid regions showing decreased ET. Cities under cold climates also evaporate more than their non‐urban surroundings during the winter, as the urban micro‐climate has increased energy availability resulting from human activities. Increased ET in arid cities arises from municipal water withdrawals and increased irrigation during drought conditions. These results can help inform planners to improve the integration of environmental conditions into the design and management of urban landscapes. Plain Language Summary: We explore and assess the impacts of urbanization on evapotranspiration (ET) fluxes across a range of landscapes from local to global spatial scales, and monthly to mean annual timescales. Remotely sensed land cover and ET data are used to quantify the differences in ET between urban and surrounding non‐urban areas. The observed patterns show the difference between urban and non‐urban ET can be estimated to first order as a function of local hydroclimate with arid/humid regions seeing increased/decreased ET due to urbanization at various time scales. Cities under cold climates also evaporate more than its non‐urban surroundings during the winter as the urban micro‐climate has increased energy availability resulting from human activity. Increased ET in arid cities arises from municipal water withdrawals and increased lawn irrigation during drought conditions further increases the ET from arid urban cities compared to non‐urban ET. Comparatively, urbanization results in decreased ET in a humid city and this magnitude substantially varies across the seasons with the spring and summer seasons being higher than the fall season and minimal changes during the winter season due to limited energy availability. This information can help to inform planners for improved environmental conditions in designing urban landscapes Key Points: Remotely sensed land cover and evapotranspiration (ET) data are used to quantify the differences in ET between urban and surrounding non‐urban areas Increased ET in arid cities arises from municipal water withdrawals Cities under cold climates also evaporate more than its non‐urban surroundings